Restoring Ravaged Heart: Molecular Mechanisms and Clinical Application of miRNA in Heart Regeneration - Shah, Vandit; Shah, Jigna (Frontiers in Cardiovascular Medicine, 2022)
Human heart development is a complex and tightly regulated process, conserving proliferation, and multipotency of embryonic cardiovascular progenitors. At terminal stage, progenitor cell type gets suppressed for terminal differentiation and maturation. In the human heart, most cardiomyocytes are terminally differentiated and so have limited proliferation capacity. MicroRNAs (miRNAs) are non-coding single-stranded RNA that regulate gene expression and mRNA silencing at the post-transcriptional level. These miRNAs play a crucial role in numerous biological events, including cardiac development, and cardiomyocyte proliferation. Several cardiac cells specific miRNAs have been discovered. Inhibition or overexpression of these miRNAs could induce cardiac regeneration, cardiac stem cell proliferation and cardiomyocyte proliferation. Clinical application of miRNAs extends to heart failure, wherein the cell cycle arrest of terminally differentiated cardiac cells inhibits the heart regeneration. The regenerative capacity of the myocardium can be enhanced by cardiomyocyte specific miRNAs controlling the cell cycle. In this review, we focus on cardiac-specific miRNAs involved in cardiac regeneration and cardiomyocyte proliferation, and their potential as a new clinical therapy for heart regeneration.